Corrigendum: Design and Experimental Study on Pneumatic Extruding Direct-writing Deposition for Multi-materials (J. Phys.: Conf. Ser. 1074 012145). (August 2018) - Ma, Ming; Chen, Peng; Zhao, Lifei; Zhang, Honghai
Abstract: Please see Article PDF for corrigendum text.